PEMERTAHANAN LEKSIKON KEMARITIMAN DALAM BAHASA MELAYU SAMBAS DI DESA JAWAI LAUT - Anbar Fitria; Ahmad Rabi’ul Muzammil; Agus Syahrani (Universitas Tanjungpura, 2019)
AbstractThis research focused on maritime lexicon in Sambas Malay language. The problem in this study was how the maritime lexicon in Sambas Malay language, the form of lingual units, language maintenance, and how the research implications for learning Indonesian. This study aimed to describe the maritime lexicon, the form of lingual units and language maintenance as well as supplementing the 2013 Indonesian language curriculum learning text. Based on the research conducted, eleven lexicon of flora, 50 lexicon fauna and ten lexicon of maritime activities were obtained. The lingual unit consists of 55 words monomorfemis, six words polymorphemis and eight phrases. The combined understanding of three generations of eleven flora lexicons in category I 93%, category II 5.7%, category III 0.3%, on 50 lexicon fauna, was obtained by understanding category I 94.20%, category II 3.73%, category III 1.9%, for the 10 activity lexicons, there was an understanding of category I 78.83%, category II 10.6%, and category III 11%. Therefore, overall maritime lexicons still survive in daily activities. The text produced in this study is a text description of the Tarah Papan Bird and the procedure text on How to Make Nets. Keywords:Language Maintenance, Lingual Unit, Maritime Lexicon,Sambas Malay language.